Claims, Debt and Equity in REA With FIBO Extensions - Bennett, Michael G.; Gillmore, Maxwell R.; Nehmer, Robert A. (Journal of Applied Business and Economics, 2022)
This paper develops a method to identify and formally model how the REA concept of Claims fits into our understanding and extension of the core REA concepts in work derived from early FIBO (Financial Industry Business Ontology) and now characterized as the Semantic Shed’s Business Core Concept Ontology (BCO). In this exploration we determine that the notion of Claim relates to two important concepts, those of some imbalance between commitments and of the perspective on such imbalances. This paper sets out the basic concepts of REA and its later extensions by the FIBO team and the Semantic Shed community, in set theoretic concept intensions. The paper goes on to define the key concepts of imbalances and of perspectives on commitments and on imbalances. We then consider the definition of ‘Claim’ in REA as a terminological challenge. Some conclusions are given about where Claim fits in with the ontological terms given here and how Equity and Debt are framed with reference to these.